Mesectodermal Leiomyoma of the Ciliary Body - Huang, Yi-Ming; Kau, Hui-Chuan; Tsai, Chieh-Chih; Kao, Shu-Ching; Lee, Fenq-Lih (Journal of Ocular Diseases and Therapeutics, 2013)
Mesectodermal leiomyoma of the ciliary body is a rare intraocular tumor. Clinically, the diagnosis of intraocular leiomyoma is challenging and the most important differential diagnosis is uveal melanoma. A 22-year-old female with high body mass index (34.5 kg/m2) presented with deteriorated vision to hand motion in left eye. Ophthalmologic examination disclosed a pigment mass in the ciliary body of the left eye and magnetic resonance imaging revealed an intraocular lobulated tumor mass with hyperintense on T1-weighted images and hypointense on T2-weighted images. Enucleation was performed because the possibility of choroidal melanoma could not be absolutely excluded. Pathological examination revealed a mesectodermal leiomyoma. Although the association between mesectodermal leiomyoma and obesity requires further investigation, this case highlights the need for including mesectodermal leiomyoma in the differential diagnosis of patients with intraocular tumor especially for young female.